INNOVATING THE SYLLABI OF LANGUAGE SKILL COURSES IN THE FACULTY OF FRENCH LANGUAGE AND CULTURE - Quang, Nguyen Viet (VNU Journal of Foreign Studies; Vol 35 No 5, 2019)
Innovating the syllabi of language skill courses is an urgent need of the Faculty of French Language and Culture. Features of newly enrolled students have many changes, so it is necessary to build appropriate syllabi. Based on the research on the application of the Common European Framework of Reference and the results of the survey on the teaching context which the courses are implemented, the author has determined the expected learning outcomes that students need to be achieved. Those rerults enables the Faculty’s academic staff to design the learning content (communication, culture and language), the teaching method, and the forms of the assessment, as well as the expected results of the learner. The courses can be applied immediately at the Faculty of French Language and Culture.